PENGEMBANGAN ALAT PRAKTIKUM PORTABLE DENGAN SENSOR LASER UNTUK PENGUKURAN GERAK - Sari, Risda Oktaviana; Partono, Partono; Alarifin, Dedy Hidayatullah (Universitas Muhammadiyah Metro, 2020)
ABSTRACT : The research (1) aims to determine the speed of moving objects on a trajectory, (2) to determine the performance of portable practicum tools with laser sensors on motion materials that are in accordance with the concept of the method, (3) to facilitate users in obtaining data, (4) to know portable practicum tools according to the principle of accuracy and practice, (5) knowing the advantages and disadvantages of the tool. This type of research is development using the ADDIE method (Analysis, Design, Development, Implementation, Evaluation). The research was conducted at the Physics Education Laboratory, Muhammadiyah Metro University. The subject of the field trial was the second semester student of UM Metro Physics Education. The object of the field trial is a portable practicum tool with a laser sensor on motion material. Types of research data in the form of quantitative and qualitative data. The data collection instruments were in the form of a media expert validation questionnaire, material experts and field trials. The data analysis technique was carried out in the form of triangulation of data by combining the obtained validation results. Based on the results of media validation obtained a percentage of 82, 98% is declared very feasible. Based on the results of material expert validation with a percentage of 88.57%, it is said to be very feasible. Based on field trial data obtained through student responses, a percentage of 82.86 was declared very feasible. From the expert validation data and field tests that have been carried out, it can be concluded that the portable practicum tool with a laser sensor on motion material is declared very feasible with a percentage obtained of 84.80%.